Obesity and serum uric acid in secondary school-age students of srinagarindra the princess mother school, Phayao, Thailand - Wanpen Suttikomin; Preeya Leelahagul; Suphawan Khamvang; Chamnong Chaimongkol; Nanticha Chaiwut (Wolters Kluwer Medknow Publications, 2018)
Background: Obesity and hyperuricemia are the precipitating factors of multiple disease processes. Studies on the relationship between obesity and hyperuricemia in Thai adolescents are limited. Objective: The objective is to investigate the gender differences in obesity and serum uric acid as well as the relationship between obesity and serum uric acid levels in secondary school-age students. Methods: A cross-sectional study conducted among 689 secondary school-age students; 313 boys and 376 girls. Body composition and fasting serum uric acid were assessed. This study defined hyperuricemia as serum uric acid >6 mg/dL in girls and >7 mg/dL in boys. Results: By body mass index (BMI) for age and percentage of body fat classification, the prevalences of obesity were 11.5% and 9.0%, respectively. Prevalence of obesity by BMI for age, 15.3% and percentage of body fat, 12.4% in boys were statistically significantly higher than those in girls, 8.2% and 6.1%, respectively. Boys in all age groups had statistically significantly higher serum uric acid levels than those in girls as well as serum uric acid levels at late adolescent period in both sexes were statistically significantly higher than those at early adolescent period. Conclusion: On multivariate analysis, the demographic factors studied showed that boys, late adolescence period, and excess body fat adolescents had higher prevalence of hyperuricemia in secondary school-age students who have their birthplace in 8 provinces of Northern Thailand. This indicated that early nutritional management and encourage obese adolescents to weight and serum uric acid reductions are important for the prevention of diet-related chronic diseases in their adult period.